Beyond the denial of death: death meditation increases a sense of connectedness and appreciation of life - Das, Enny; Fransen, Marieke L.; Oliver, Mary Beth (Frontiers in Psychiatry, 2024)
IntroductionThe pervasive denial of death in modern society has created an unbalanced relationship with death that gets in the way of living a full life. To address this problem, the Lancet Commission on the Value of Death recently proposed principles of a healthier scenario for the future. In this ‘realistic utopia’, death is recognized as having value, and conversations about death and dying have become common. The present research examined if art could help to decrease death denial and increase life appreciation.MethodsAn art installation invited visitors to confront thoughts of their own death in a guided meditation by visualizing the decay of their own dead body. Visitors’ responses were compared to those of a standard death reflection group and a neutral control group (N=229) at two time points. Feelings of being moved, connectedness to a higher power, and life appreciation were assessed immediately (T1); death reflection and life appreciation were assessed two weeks later (T2) (N=105).ResultsAt T1, the art installation induced higher levels of being moved and connectedness to a higher power than the two control groups. At T2, the art installation induced more lingering reflection than the two control groups. Lingering reflection, in turn, increased appreciation of life.DiscussionWe show that art can be harnessed to promote a more balanced relationship with death, and greater appreciation of life. The art installation provided individuals with concrete, and more encompassing simulations of what death could be like. By placing death in this bigger perspective, the art installation encouraged conscious death reflection. Such a connected perspective is often lacking, but direly needed, in healthcare and in larger society.